From monolingualism to multilingualism: the case of Bunjevci from Bačka - Vuković, Petar, lingvist (Array, 2011)
After the break-up of Yugoslavia, the language that was referred to as Serbo-Croatian officially came to its end. On the basis of what were earlier considered to be its eastern and western variants, two distinct standard languages – Croatian and Serbian – have been established, while in the interspace another two – Bosnian and Montenegrin – have emerged. Since 2004 they have been followed by Bunjevac, the smallest and the most disputed of the languages that arose on the ruins of Serbo-Croatian. Bunjevci are a South Slavic (sub)ethnic group originating from Dalmatia and Herzegovina, which at the end of the sixteenth century started migrating to the west and north and by the beginning of the nineteenth was scattered over the area between the Adriatic Sea and Buda. In the largest part of this area, Bunjevci were assimilated to the neighbouring ethnic groups, and only in some parts of Croatia and in the region of Bačka, which is now divided between Serbia and Hungary, there are still dozens of thousands of people who identify themselves as Bunjevci. However, while Bunjevci in Croatia claim that they are merely a subgroup of Croats, in Bačka they are not unanimous about their collective identity. While some of them do consider themselves to be Croats who just speak a specific dialect, others take the view that Bunjevci are a separate ethnic group (or even nation) with a distinct language. In the paper, sociolinguistic situation among Bunjevci in Bačka and current attempts to standardize Bunjevac language will be approached from a wider perspective. In the first step, a dialect map of the central South Slavic area will be sketched, and in the next, the history of literacy and the spread of modern nationalism in the area will be presented. This should help the reader to understand better the specific development of ethnic consciousness and the unique sociolinguistic situation among Bunjevci, which will be dealt with in the third step. The analysis will be concluded by comparing current linguistic activism among Bunjevci to the efforts made in some other minority groups in Europe in order to preserve their own language varieties in the era of globalization.